Fiber-reinforced sheet

The fiber reinforced sheet with powders attached to the outer periphery of fiber reinforced plastic wires addresses the adhesion issues in existing reinforcement methods, enhancing the adhesion and preventing peeling off, thereby ensuring effective reinforcement.

JP2025070864APending Publication Date: 2025-05-02NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023181451
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing fiber reinforced sheet reinforcement methods face issues with insufficient adhesion between the fiber reinforced sheet and the binder, particularly when using inorganic binders, leading to peeling off before reaching the breaking strength.

Method used

A fiber reinforced sheet is developed with multiple fiber reinforced plastic wires pulled in a slit shape and fixed with a wire fixing material, where powders with an average particle diameter of 0.900 mm or less are attached to the outer periphery of the wires, ensuring a minimum gap of 0.5 mm between adjacent wires.

Benefits of technology

The anti-slip effect of the powder enhances adhesion between the fiber reinforced sheet and the binder, preventing peeling off before reaching the breaking strength, while maintaining a suitable gap spacing for effective reinforcement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025070864000001_ABST
    Figure 2025070864000001_ABST
Patent Text Reader

Abstract

To provide a fiber-reinforced sheet that can firmly adhere by itself to a binder even when the binder is an inorganic system, and can suppress the sheet from peeling off from the binder before reaching its breaking strength.SOLUTION: In a fiber-reinforced sheet, disclosed is a fiber-reinforced sheet that is buried in a binder coated on a surface of a structure so as to be stuck to the surface, in which a plurality of fiber-reinforced plastic wires containing a reinforcement fiber is set in a reed screen shape in the longer direction, the fiber-reinforced plastic wires are fixed mutually by using a wire fixing material, powder having an average grain size of 0.900 mm or under is attached to a circumference of the fiber-reinforced plastic wires at a rate of 0.2-2.0 kg / m2, and the minimum gap interval of the powder being attached in the fiber-reinforced plastic wires that are adjacent to each other is 0.5 mm or over.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a fiber-reinforced sheet. [Background technology]

[0002] In recent years, methods of reinforcing existing or newly constructed structures have become known, such as the carbon fiber sheet bonding method and aramid fiber sheet bonding method described in Patent Document 1, in which a continuous fiber-reinforced sheet such as a carbon fiber sheet or an aramid fiber sheet is attached to or wrapped around the surface of the structure, or a method in which a sheet in which a continuous fiber bundle is impregnated with an uncured matrix resin is bonded and then cured.

[0003] Furthermore, Patent Documents 2 and 3 disclose a method of reinforcing a structure, in which a plurality of continuous fiber-reinforced plastic wires, which have been impregnated with a matrix resin and hardened, are aligned in the longitudinal direction like a curtain, and the wires are fixed to each other with a wire fixing material to form a fiber-reinforced sheet, which is then bonded to the surface of the structure with a bonding material to form an integrated structure. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 3-224901 [Patent Document 2] Japanese Patent Application Laid-Open No. 2008-63758 [Patent Document 3] Japanese Patent Application Laid-Open No. 2011-208352 Summary of the Invention [Problem to be solved by the invention]

[0005] In the reinforcement methods disclosed in Patent Documents 2 and 3, in which a fiber-reinforced sheet is bonded to the surface of a structure with a binder, if the adhesion between the fiber-reinforced sheet and the binder is insufficient, the fiber-reinforced sheet may peel off from the binder before reaching its breaking strength. This phenomenon occurs more significantly when the binder is an inorganic binder than when it is a resin-based binder.

[0006] An object of the present invention is to provide a fiber-reinforced sheet that can firmly adhere to a binder even if the binder is inorganic, and can prevent the sheet from peeling off from the binder before reaching its breaking strength. [Means for solving the problem]

[0007] The fiber-reinforced sheet of the first embodiment is a fiber-reinforced sheet that is adhered to a surface of a structure by being embedded in a binder applied to the surface of the structure, and is made up of a plurality of fiber-reinforced plastic strands containing reinforcing fibers that are aligned in a longitudinal direction like a curtain, the fiber-reinforced plastic strands being fixed to each other with a wire fixing material, and a powder having an average particle size of 0.900 mm or less that is applied to the outer periphery of the plurality of fiber-reinforced plastic strands at a rate of 0.2 to 2.0 kg / m 2 The powder is adhered to the adjacent fiber-reinforced plastic strands with a minimum gap of 0.5 mm or more.

[0008] In the fiber-reinforced sheet of the first embodiment, the powder adheres to the outer periphery of a plurality of fiber-reinforced plastic strands, and the powder acts as an anchor to the binder, providing an anti-slip effect that enhances adhesion between the fiber-reinforced sheet and the binder. As a result, the fiber-reinforced sheet is firmly bonded to the binder, and peeling of the fiber-reinforced sheet from the binder before it breaks can be suppressed.

[0009] Here, the amount of powder attached to the outer periphery of the multiple fiber-reinforced plastic wires is 0.2 kg / m 2If the powder is less than 1000 kJ / cm, the anti-slip effect of the powder acting as an anchor is small, and the force acting on the attached powder particles is large, resulting in low adhesion between the fiber-reinforced sheet and the binder, which may cause the fiber-reinforced sheet to break or peel off from the binder before the binder is destroyed.

[0010] In contrast, in the fiber-reinforced sheet of the first embodiment, the powder is applied at 0.2 kg / m around the periphery of the plurality of fiber-reinforced plastic strands. 2 Since the powder adheres to the surface, the anti-slip effect of the powder maintains high adhesion between the fiber reinforced sheet and the binder.

[0011] Here, the fiber-reinforced sheet is a sheet made by aligning multiple fiber-reinforced plastic strands in a curtain-like shape in the longitudinal direction, so when powder is attached to the outer periphery of the multiple fiber-reinforced plastic strands, the spaces between the multiple fiber-reinforced plastic strands become narrower.

[0012] In contrast, in the fiber-reinforced sheet of the first embodiment, the powder is applied to the periphery of the plurality of fiber-reinforced plastic strands at a pressure of 2.0 kg / m 2 The fibers are attached at a minimum spacing of 0.5 mm or more, and the average particle size of the powder is 0.900 mm or less. Therefore, when the fiber-reinforced sheet is embedded and bonded in the binder applied to the surface of the structure, the binder easily passes through the gaps between the fiber-reinforced plastic strands even if the gaps are narrow. As a result, poor installation (poor adhesion between the fiber-reinforced sheet and the binder) is suppressed, and the fiber-reinforced sheet is prevented from peeling off from the binder before breaking.

[0013] In the fiber reinforced sheet of the second embodiment, in the first embodiment, the gap distance between the fiber reinforced plastic strands, ignoring the powder, is more than 3 mm and 15 mm or less.

[0014] Here, when the gap spacing between the fiber-reinforced plastic wires is 3 mm or less, the gaps between the fiber-reinforced plastic wires are narrow, and it is difficult to adjust the minimum gap spacing to 0.5 mm or more for multiple fiber-reinforced plastic wires with powder attached to the outer periphery.

[0015] On the other hand, if the gap distance between the fiber-reinforced plastic strands exceeds 15 mm, the number of fiber-reinforced plastic strands per unit area of ​​the fiber-reinforced sheet decreases, and the reinforcing effect decreases.

[0016] In contrast, in the second aspect, as mentioned above, the gap spacing between the fiber-reinforced plastic strands in the fiber-reinforced sheet is greater than 3 mm and not greater than 15 mm, making it easy to adjust the minimum gap spacing to 0.5 mm or more while suppressing a decrease in the reinforcing effect.

[0017] In the fiber-reinforced sheet of the third embodiment, in the first or second embodiment, the gap spacing between the fiber-reinforced plastic strands, ignoring the powder, is larger than the diameter of the powder, and the ratio of the diameter of the fiber-reinforced plastic strand, the gap spacing ignoring the powder, and the diameter of the powder is 1:0.5 to 5:0.03 to 1.

[0018] Here, if the ratio of the gap spacing between the fiber-reinforced plastic strands to the diameter of the fiber-reinforced plastic strands is less than 0.5, the spacing between the fiber-reinforced plastic strands will be relatively narrow, making it difficult for the binder to pass between the fiber-reinforced plastic strands.

[0019] On the other hand, if the ratio of the gap spacing between the fiber-reinforced plastic strands to the diameter of the fiber-reinforced plastic strands exceeds 5, the area of ​​the fiber-reinforced plastic strands per unit area of ​​the fiber-reinforced sheet decreases, and the reinforcing effect decreases.

[0020] Furthermore, if the ratio of the diameter of the powder to the diameter of the fiber-reinforced plastic strand is less than 0.03, the anti-slip effect of the powder is small, and the adhesion between the fiber-reinforced sheet and the binder is low, which can cause the fiber-reinforced sheet to peel off from the binder before reaching its breaking strength.

[0021] On the other hand, if the ratio of the powder diameter to the fiber-reinforced plastic strand diameter exceeds 1, the spaces between the fiber-reinforced plastic strands become narrower. As a result, it becomes difficult for the binder to pass through the spaces between the fiber-reinforced plastic strands, which can lead to poor installation.

[0022] In contrast, in the third aspect, as described above, the ratio of the diameter of the fiber-reinforced plastic strand, the gap between the fiber-reinforced plastic strands, and the diameter of the powder is 1:0.5 to 5:0.03 to 1, so the anti-slip effect of the powder maintains high adhesion between the fiber-reinforced sheet and the binder, making it easier for the binder to pass between the fiber-reinforced plastic strands.

[0023] As a result, poor application (poor adhesion between the fiber reinforced sheet and the binder) is suppressed, and the fiber reinforced sheet is prevented from peeling off from the binder before it reaches its breaking strength.

[0024] As the fiber-reinforced sheet of the fourth aspect, in any one of the first to third aspects, the powder can be either No. 4 to No. 8 silica sand and a mixture thereof, or 1 to 2 rin limestone powder and a mixture thereof.

[0025] As the fiber-reinforced sheet of the fifth aspect, in any one of the first to fourth aspects, the fiber-reinforced plastic strand can be made into a yarn formed by twisting together a plurality of fiber bundles in which the reinforcing fibers are aligned in one direction.

[0026] As a fiber-reinforced sheet of the sixth aspect, in any one of the first to fifth aspects, the wire fixing material can be a plurality of weft threads that weave together a plurality of fiber-reinforced plastic wires in a direction perpendicular to the longitudinal direction of the fiber-reinforced plastic wires.

[0027] In the fiber-reinforced sheet of the seventh embodiment, in the sixth embodiment, the weft yarns can be threads made of glass fiber or organic fiber.

[0028] As the fiber-reinforced sheet of the eighth aspect, in any one of the first to seventh aspects, the reinforcing fibers of the fiber-reinforced plastic strand may be one of inorganic fibers selected from carbon fiber, glass fiber, basalt fiber, and fly ash fiber, metal fibers selected from boron fiber, titanium fiber, and steel fiber, and organic fibers selected from aramid, polyparaphenylene benzbisoxazole, polyamide, polyarylate, and polyester, either alone or in combination.

[0029] As the fiber-reinforced sheet of the ninth aspect, in any one of the first to eighth aspects, the fiber-reinforced plastic strand is formed by curing a matrix resin impregnated into the reinforcing fibers, and the matrix resin can be a thermosetting resin selected from room temperature curing or thermosetting epoxy resin, vinyl ester resin, acrylic resin, unsaturated polyester resin, and phenolic resin, or a thermoplastic resin selected from nylon, vinylon, and phenoxy resin. [Brief explanation of the drawings]

[0030] [Figure 1] 1 is a schematic cross-sectional view showing a state in which a fiber-reinforced sheet is bonded to the surface of a structure with a binder by a reinforcing method according to the present embodiment. FIG. [Figure 2] 10 is a schematic cross-sectional view for explaining a base treatment step in the reinforcing method according to the embodiment. FIG. [Figure 3] FIG. 4 is a schematic cross-sectional view illustrating a primer application step in the reinforcement method according to the present embodiment. [Figure 4] FIG. 10 is a schematic cross-sectional view illustrating a mortar application step in the reinforcing method according to the present embodiment. [Figure 5] FIG. 1A shows a fiber-reinforced sheet according to the present embodiment, and FIG. 1B shows a fiber-reinforced plastic strand of the fiber-reinforced sheet according to the present embodiment. [Figure 6] 1 is a table showing the average particle size of various powders. [Figure 7] FIG. 1 is a schematic diagram of a test piece for a single-sided tensile shear test. [Figure 8] FIG. 1 is an explanatory diagram of a one-way shear test. [Figure 9] Table 1 shows the evaluation results. [Figure 10] 1 is a cross-sectional view showing a cross section of a fiber-reinforced sheet according to an embodiment of the present invention. [Figure 11] FIG. 1 is a diagram showing an outline of a testing machine for a deck wheel load running test. [Figure 12] FIG. 10 is a diagram showing the state in which a fiber-reinforced sheet is placed on a test specimen in a deck wheel load running test. [Figure 13] FIG. 1 is a diagram showing a test specimen used in a deck wheel load running test. [Figure 14] 1 is a table showing the concrete mix of the test specimen used in the deck wheel load running test. [Figure 15] 10 is a graph showing loading conditions in a deck wheel load running test. [Figure 16] 10 is a graph showing test results of a deck wheel load running test. DETAILED DESCRIPTION OF THE INVENTION

[0031] An example of an embodiment of the present invention will be described below with reference to the drawings.

[0032] In this specification, a numerical range indicated using "to" means a range that includes the numerical values ​​before and after "to" as the minimum and maximum values, respectively. Furthermore, in the numerical ranges described in stages in this specification, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. Furthermore, in the numerical ranges described in this specification, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples. In this specification, when multiple substances corresponding to each component exist, the amount of each component means the total amount of multiple substances, unless otherwise specified.

[0033] <Reinforcement method> 1, the reinforcement method according to this embodiment is a method for reinforcing a structure 90 (fiber-reinforced sheet bonding method) in which a fiber-reinforced sheet 40 is bonded to a surface 90A of the structure 90 with a binder. In fiber-reinforced sheet bonding methods, a resin-based binder such as epoxy resin is generally used as the binder. However, in the reinforcement method according to this embodiment, it has been discovered that by using an aqueous epoxy primer 20, polymer cement mortar 50 as the binder, and the fiber-reinforced sheet 40, it is possible to reinforce the structure 90 without using hazardous materials (combustible materials) as defined by the Fire Service Act.

[0034] The following will first explain the structure 90, the water-based epoxy primer 20, the polymer cement mortar 50, and the fiber-reinforced sheet 40. Then, the steps of the reinforcing method, the effects of the fiber-reinforced sheet 40, and an evaluation of the fiber-reinforced sheet 40 will be explained.

[0035] <Structure 90> The structure 90 to be reinforced by the reinforcing method according to this embodiment may be, for example, a concrete structure. Examples of concrete structures include bridge decks. Examples of concrete structures include reinforced concrete structures with reinforcing bars inside and unreinforced concrete structures without reinforcing bars inside.

[0036] Concrete structures are not limited to bridge decks, but may include structures other than bridge decks (such as bridge girders and piers), tunnels, buildings, etc., as long as they are made of concrete.

[0037] Furthermore, the structure 90 is not limited to a concrete structure, but may be, for example, a structure made of mortar, ceramics, metal, glass, or the like, as long as it is a structure to be reinforced.

[0038] Hereinafter, the surface 90A of the structure 90 reinforced by the reinforcing method according to this embodiment may be referred to as the surface to be reinforced 90A. The surface to be reinforced 90A is, for example, the bottom surface of the structure 90 facing downward (specifically, downward in the direction of gravity). The surface to be reinforced 90A may also be a side surface of the structure 90 (specifically, a surface along the direction of gravity or a surface inclined with respect to the direction of gravity), and in this embodiment, the surface to be reinforced 90A is, for example, a surface on which dripping of the polymer cement mortar 50 may occur (i.e., a surface excluding a horizontal surface facing upward in the direction of gravity).

[0039] <Water-based epoxy primer 20> The water-based epoxy primer 20 is an epoxy resin primer using water as a medium. It has the advantage of having higher shear strength than water-based acrylic primers, and therefore is used in the present invention. Water-based epoxy primers are available in emulsion types and those using water-soluble epoxy resins, each of which is available in one-component and two-component curing types. The preferred water-based epoxy primer 20 used in the present invention is a two-component emulsion-type primer containing an emulsion-type epoxy resin base and a curing agent. Water-based epoxy primer 20 can be formulated in a predetermined ratio depending on the materials used (e.g., a 100:100 weight ratio of base resin and curing agent). Furthermore, from the perspective of repairing concrete structures, a viscosity of 100 mPa·s or less is preferred for enhanced penetration.

[0040] Specifically, as the water-based epoxy primer 20, for example, FP Primer FP-EE from Nippon Steel Chemical & Material Co., Ltd. can be used.

[0041] <Polymer cement mortar 50> The polymer cement mortar 50 is a cement composite material containing cement, fine aggregate, a cement-mixing polymer, and reinforcing organic fibers.

[0042] The cement can be selected taking into consideration the construction conditions at the site and is not particularly limited. For example, various Portland cements such as ordinary, early strength, medium heat and extra early strength, various mixed cements such as blast furnace cement in which fly ash or blast furnace slag is mixed with these various Portland cements, rapid hardening cements, etc. can be used alone or in combination of two or more types.

[0043] In addition, known admixtures such as blast furnace slag powder, fly ash, silica fume, limestone powder, quartz powder, gypsum dihydrate, gypsum hemihydrate, anhydrous gypsum, quicklime-based expanding materials, and calcium sulfoaluminate-based expanding materials can be added to the cement.

[0044] Examples of fine aggregates that can be used include river sand, sea sand, mountain sand, crushed sand, No. 3 to No. 8 silica sand, limestone, and slag fine aggregate. It is preferable to use fine aggregates such as sized silica sand and limestone that do not contain fine powder or coarse aggregate. The blending ratio can be 25 to 300 parts by mass, preferably 50 to 230 parts by mass, per 100 parts by mass of the cement.

[0045] Examples of polymers for cement admixture include liquid polymer emulsions and re-emulsified powder resins, and those specified in JIS A 6203 can be used, for example. Specific examples include resins such as polyacrylic ester, styrene butadiene, ethylene vinyl acetate, vinyl acetate / versatate vinyl ester, and vinyl acetate / versatate vinyl ester / acrylic ester, and any of these can be appropriately selected and used alone or in combination as an emulsion.

[0046] Examples of reinforcing organic fibers include ultra-high molecular weight polyethylene fibers, vinylon fibers, nylon fibers, polyparaphenylene benzobisoxazole fibers (PBO fibers), para-aramid fibers, and polyarylate fibers, and these can be used alone or in combination of two or more.

[0047] In addition to the above materials, polymer cement mortar 50 may contain additives such as a setting retarder, a hardening accelerator, a thickener, an antifoaming agent, a foaming agent, an anti-rust agent, an antifreeze agent, a colorant, a water retention agent, a shrinkage reducing agent, and an expansion agent.

[0048] In this embodiment, polymer cement mortar 50 is a cement composite material having a flow value of 140 to 180 mm in the JIS flow test and a sagging amount of 10 mm or less in the JHS-416-2004 Section Repair Material Quality Standard Test Method.

[0049] The JIS flow test is a flow test conforming to JIS R 5201. If the flow value is less than 140 m, the fluidity of polymer cement mortar 50 decreases, making it difficult for polymer cement mortar 50 to pass between fiber-reinforced plastic wires 43 to which powder is attached in fiber-reinforced sheet 40. If the flow value exceeds 180 m, polymer cement mortar 50 is likely to drip from reinforced surface 90A.

[0050] In this embodiment, a cement composite material having a flow value of 140 to 180 mm in the JIS flow test is used, as described above, from the viewpoint of preventing dripping of polymer cement mortar 50 from reinforced surface 90A while ensuring the fluidity of polymer cement mortar 50. Furthermore, from the above viewpoint, it is preferable to use a cement composite material having a flow value of 150 to 170 mm in the JIS flow test.

[0051] In addition, polymer cement mortar 50 had a tensile strength of 2.5 N / mm in a uniaxial direct tensile strength test at 28 days. 2 This cement composite material has a tensile stress of 35% or more of the tensile strength when the tensile strain reaches 1.5% in the same test.

[0052] The tensile strength in the uniaxial direct tensile strength test at 28 days was 2.5N / mm 2If the tensile stress is less than 35% of the tensile strength when the tensile strain reaches 1.5% in the test, cracks (fracture) are likely to occur when tensile stress is generated in the fiber-reinforced sheet 40 due to deflection of the structure, and the fiber-reinforced sheet 40 may peel off from the bonding material before breaking.

[0053] In this embodiment, from the viewpoint of suppressing the occurrence of cracks (fractures) when tensile stress is applied to fiber-reinforced sheet 40, as described above, polymer cement mortar 50 is selected from those having a tensile strength of 2.5 N / mm 2 in a uniaxial direct tensile strength test at a material age of 28 days. 2 The cement composite material used must have a tensile stress of 35% or more of its tensile strength when it reaches a tensile strain of 1.5% in the test. Furthermore, from the above perspective, the tensile strength must be 3.0 N / mm in a uniaxial direct tensile strength test at 28 days. 2 From the above viewpoint, it is preferable to use a cement composite material in which the tensile stress at a tensile strain of 1.5% in the test is 50% or more of the tensile strength.

[0054] The content of the reinforcing organic fibers in polymer cement mortar 50 is 0.9 to 1.5 vol %. If the content of the reinforcing organic fibers in polymer cement mortar 50 is less than 0.9 vol %, cracks (fracture) are likely to occur in polymer cement mortar 50, which serves as a binder, when stress is generated in fiber reinforced sheet 40. If cracks (fracture) occur in polymer cement mortar 50, it will not be able to perform its function as a binder, and fiber reinforced sheet 40 may peel off from the binder before breaking.

[0055] On the other hand, if the reinforcing organic fiber contained in polymer cement mortar 50 exceeds 1.5 vol%, the viscosity of polymer cement mortar 50 increases extremely, making it difficult for polymer cement mortar 50 to pass between the fiber-reinforced plastic wires of fiber-reinforced sheet 40, which may result in poor installation.

[0056] In this embodiment, as described above, the content of reinforcing organic fibers in polymer cement mortar 50 is set to 0.9 to 1.5 vol % from the viewpoint of ensuring the fluidity of polymer cement mortar 50 while suppressing cracking (fracture) of polymer cement mortar 50. From the above viewpoint, the content of reinforcing organic fibers in polymer cement mortar 50 is preferably 1.0 to 1.3 vol %.

[0057] The reinforcing organic fibers contained in polymer cement mortar 50 have a fiber length of 6 to 12 mm and an aspect ratio of 120 to 1200. If the reinforcing organic fibers contained in polymer cement mortar 50 have a fiber length of less than 6 mm or an aspect ratio of less than 120, cracks (fracture) are likely to occur in polymer cement mortar 50, which serves as a binder, when stress is generated in fiber-reinforced sheet 40. If cracks (fracture) occur in polymer cement mortar 50, it will not be able to perform as a binder, and fiber-reinforced sheet 40 may peel off from the binder before breaking.

[0058] On the other hand, if the fiber length of the reinforcing organic fibers contained in polymer cement mortar 50 exceeds 12 mm, or if the aspect ratio of the reinforcing organic fibers exceeds 1200, the viscosity of polymer cement mortar 50 increases extremely, making it difficult for polymer cement mortar 50 to pass between the fiber-reinforced plastic wires of fiber-reinforced sheet 40, which may result in poor application.

[0059] In this embodiment, from the viewpoint of ensuring the fluidity of polymer cement mortar 50 while suppressing cracking (fracture) of polymer cement mortar 50, as described above, the reinforcing organic fibers contained in polymer cement mortar 50 have a fiber length of 6 to 12 mm and an aspect ratio of 120 to 1200. From the above viewpoint, it is preferable that the reinforcing organic fibers contained in polymer cement mortar 50 have a fiber length of 8 to 10 mm. From the above viewpoint, it is preferable that the reinforcing organic fibers contained in polymer cement mortar 50 have an aspect ratio of 300 to 1000.

[0060] Polymer cement mortar 50 contains fine aggregate, the maximum diameter of which is 0.2 to 1.2 mm, and the fine aggregate fraction (FM) value is 0.5 to 2.3. If the maximum diameter of the fine aggregate is less than 0.2 mm, or if the fine aggregate fraction (FM) value is less than 0.5, the viscosity of polymer cement mortar 50 increases significantly, making it difficult to mix with a mixer.

[0061] On the other hand, if the maximum diameter of the fine aggregate exceeds 1.2 mm, it may be difficult for polymer cement mortar 50 to pass through between the fiber reinforced plastic wires of fiber reinforced sheet 40, which may result in poor construction.

[0062] Furthermore, if the fineness factor (FM) value exceeds 2.3, the viscosity of polymer cement mortar 50 increases extremely, making it difficult for polymer cement mortar 50 to pass between the fiber-reinforced plastic wires of fiber-reinforced sheet 40, which may result in poor construction.

[0063] In this embodiment, from the viewpoint of preventing poor construction, as described above, polymer cement mortar 50 has fine aggregate with a maximum diameter of 0.2 to 1.2 mm and a fine particle fraction (FM) value of 0.5 to 2.3. From the above viewpoint, it is preferable that the fine aggregate has a maximum diameter of 0.3 to 1.0 mm. From the above viewpoint, it is preferable that the fine particle fraction (FM) value is 0.8 to 2.0.

[0064] <Fiber reinforced sheet 40> 1 , the fiber-reinforced sheet 40 is a sheet material that is bonded to a surface 90A to be reinforced of a structure 90 with polymer cement mortar 50 as a binder, thereby reinforcing the structure 90. Specifically, the fiber-reinforced sheet 40 is bonded to the surface 90A to be reinforced by being embedded in the polymer cement mortar 50 that has been applied to the surface 90A to be reinforced of the structure 90. In this embodiment, the fiber-reinforced sheet 40 is disposed inside a binder layer 52 made of the polymer cement mortar 50.

[0065] 5(A), this fiber-reinforced sheet 40 is a fiber-reinforced sheet 40 in which a plurality of fiber-reinforced plastic strands 43 containing reinforcing fibers 42 are aligned in a curtain-like shape in the longitudinal direction and the fiber-reinforced plastic strands 43 are fixed to each other with a wire fixing material 45. Furthermore, in the fiber-reinforced sheet 40, powder is attached to the outer periphery of the plurality of fiber-reinforced plastic strands 43.

[0066] The reinforcing fibers 42 may be, for example, inorganic fibers selected from carbon fibers, glass fibers, basalt fibers, fly ash fibers, etc.; metal fibers selected from boron fibers, titanium fibers, steel fibers, etc.; or organic fibers selected from aramid, polyparaphenylene benzbisoxazole, polyamide, polyarylate, polyester, etc., either alone or in combination. However, examples of reinforcing fibers are not limited to these fibers.

[0067] Specifically, as shown in Figures 5(A) and 5(B), the fiber-reinforced sheet 40 may be a fiber sheet (so-called strand sheet) in which a plurality of fiber-reinforced plastic strands 43 containing reinforcing fibers 42 are aligned in the longitudinal direction in a curtain-like shape and fixed to one another by a plurality of wire fixing materials 45 that serve as wefts weaving the plurality of fiber-reinforced plastic strands 43 in a direction perpendicular to the longitudinal direction. The wefts that make up the wire fixing material 45 are threads made of, for example, glass fiber or organic fiber. However, the wefts that make up the wire fixing material 45 are not limited to these fibers.

[0068] The fiber-reinforced plastic strand 43 is a yarn formed by twisting together a plurality of fiber bundles in which the reinforcing fibers 42 are aligned in one direction (longitudinal direction). Note that the fiber-reinforced sheet 40 may also be an untwisted yarn in which the reinforcing fibers 42 are aligned in one direction (longitudinal direction).

[0069] 5(B), the fiber-reinforced plastic strand 43 is formed by impregnating the reinforcing fibers 42 with a matrix resin 47 and then curing the matrix resin 47. The matrix resin 47 is a thermosetting resin selected from room-temperature curing or thermosetting epoxy resins, vinyl ester resins, acrylic resins, unsaturated polyester resins, and phenolic resins, or a thermoplastic resin selected from nylon, vinylon, and phenoxy resins, with epoxy resin being a preferred thermosetting resin.

[0070] In the fiber-reinforced sheet 40, the gap between the fiber-reinforced plastic strands 43 is more than 3 mm and not more than 15 mm. Note that this gap is the gap S2 that does not take into account powder between the fiber-reinforced plastic strands 43 (see FIG. 10).

[0071] <Powder used in the fiber-reinforced sheet 40> The powder adhering to the fiber reinforced sheet 40 has an average particle size of 0.900 mm or less, and is 0.2 to 2 kg / m 2 per unit area of ​​the fiber reinforced sheet 40. 2 If the powder adhering to the fiber-reinforced sheet 40 has an average particle size of more than 0.900 mm, the powder will get caught on the rubber spatula when the fiber-reinforced sheet 40 is pressed down to embed it, which reduces workability, and the amount of powder adhering to the unit area of ​​the fiber-reinforced sheet 40 will exceed 0.2 kg / m. 2 If the average particle size is less than 0.07 mm, the powder acting as an anchor has little anti-slip effect, and the force acting on the attached powder particles is large, resulting in poor adhesion between the fiber-reinforced sheet 40 and the polymer cement mortar 50. As a result, the fiber-reinforced sheet 40 may peel off from the binder before breaking. While there is no particular lower limit for the average particle size, if the average particle size is too small, the safety, workability, and material costs of the attachment work to the fiber-reinforced sheet are adversely affected. Therefore, it is preferable that the average particle size be set to 0.07 mm or more. Furthermore, the amount of powder attached to the fiber-reinforced sheet 40 is preferably 0.4 kg / m. 2 That's all.

[0072] In addition, when the powder adhering to the fiber reinforced sheet 40 has an average particle size exceeding 0.900 mm, or when the amount of adhesion per unit area of ​​the fiber reinforced sheet 40 is 2 kg / m 2 If it exceeds this value, the gaps between fiber-reinforced plastic strands 43 become narrower. As a result, it becomes difficult for polymer cement mortar 50 to pass through gaps between fiber-reinforced plastic strands 43 of fiber-reinforced sheet 40, which may result in poor application.

[0073] The minimum gap between adjacent fiber-reinforced plastic strands 43 in the fiber-reinforced sheet 40 in a powder-adhered state is 0.5 mm or more and 10 mm or less. This gap is the gap S1 between the powder-containing fiber-reinforced plastic strands 43 (see FIG. 10).

[0074] If the minimum gap distance is less than 0.5 mm, the gaps between fiber reinforced plastic strands 43 are narrow, making it difficult for polymer cement mortar 50 to pass between fiber reinforced plastic strands 43 of fiber reinforced sheet 40 .

[0075] On the other hand, if the minimum gap between the fiber reinforced plastic strands 43 exceeds 10 mm, the number of fiber reinforced plastic strands per unit area of ​​the fiber reinforced sheet decreases, and the reinforcing effect decreases.

[0076] In this embodiment, as described above, the minimum gap distance S1 is set to 0.5 mm or more and 10 mm or less from the viewpoints of ease of adjustment of the minimum gap distance and the reinforcing effect of the fiber reinforced sheet 40. Furthermore, from the above viewpoints, it is preferable that the minimum distance S1 be 0.5 mm or more and 5.5 mm or less.

[0077] The fiber reinforced plastic strands 43 have a diameter larger than that of the powder, and the ratio of the diameter of the fiber reinforced plastic strands 43 in the fiber reinforced sheet 40, the gap between the fiber reinforced plastic strands 43, and the diameter of the powder is 1:0.5-5:0.03-1.

[0078] 10, the diameter of the fiber-reinforced plastic strand 43 is indicated by diameter D2, and the diameter of the powder is indicated by diameter D1. Also, in Fig. 10, the minimum gap between the fiber-reinforced plastic strands 43 in a powder-adhered state is indicated by gap S1, the gap between the fiber-reinforced plastic strands 43 (the gap between the fiber-reinforced plastic strands 43 not taking into account the powder) is indicated by gap S2, and the installation interval between the fiber-reinforced plastic strands 43 (the distance between the centers of the fiber-reinforced plastic strands 43) is indicated by gap S3. Fig. 10 is a diagram schematically showing the fiber-reinforced plastic strands 43 and the powder, and in reality, the powder is adhered to the outer periphery of the fiber-reinforced plastic strand 43.

[0079] If the ratio of the spacing between fiber-reinforced plastic wires 43 to the diameter of fiber-reinforced plastic wires 43 is less than 0.5, the spaces between fiber-reinforced plastic wires 43 are relatively narrow, making it difficult for polymer cement mortar 50 to pass between fiber-reinforced plastic wires 43 of fiber-reinforced sheet 40.

[0080] On the other hand, if the ratio of the spacing between the fiber-reinforced plastic wires 43 to the diameter of the fiber-reinforced plastic wires 43 exceeds 5, the area of ​​the fiber-reinforced plastic wires 43 per unit area of ​​the fiber-reinforced sheet 40 decreases, and the reinforcing effect decreases.

[0081] Furthermore, if the ratio of the diameter of the powder to the diameter of fiber-reinforced plastic strands 43 is less than 0.03, the anti-slip effect of the powder is small, and the adhesion between fiber-reinforced sheet 40 and polymer cement mortar 50 is low. As a result, fiber-reinforced sheet 40 may peel off from the binder before breaking.

[0082] On the other hand, if the ratio of the diameter of the powder to the diameter of the fiber-reinforced plastic strands 43 exceeds 1, the spaces between the fiber-reinforced plastic strands 43 become narrower. As a result, it becomes difficult for the polymer cement mortar 50 to pass through the spaces between the fiber-reinforced plastic strands 43 of the fiber-reinforced sheet 40, which may result in poor application.

[0083] The ratio of the diameter of the fiber reinforced plastic strands 43 of the fiber reinforced sheet 40, the spacing between the fiber reinforced plastic strands 43, and the diameter of the powder is preferably 1:0.5-5:0.1-1.

[0084] The powder has an average particle size (D50) of 0.90 mm or less in the particle size distribution measured according to JIS Z 2601, and may be made of not only inorganic materials but also organic materials such as synthetic resins, but from the viewpoint of preventing the strand sheet from being pulled out due to the destruction of the powder particles themselves, it is preferable that the powder has a Mohs hardness of 3 or more, and is more preferably made of inorganic materials.Specific examples include crushed silica sand selected from No. 4 silica sand (average particle size: 0.887 mm), No. 5 silica sand (average particle size: 0.511 mm), No. 6 silica sand (average particle size: 0.294 mm), No. 7 silica sand (average particle size: 0.129 mm), No. 8 silica sand (average particle size: 0.073 mm), or a mixture thereof, crushed limestone selected from Hakuryu crushed stone of 1 rin (average particle size: 0.4 mm) or 2 rin (average particle size: 0.7 mm), and the like, The materials are fine aggregates of blast furnace slag of similar particle size, fine aggregates of natural materials such as river sand, sea sand, mountain sand, and crushed sand, fine powders of ceramic materials such as graphite, silica, and alumina, or mixtures thereof, but considering cost and workability, silica sand selected from No. 4, No. 5, No. 6, and No. 7 silica sand, or 1-rin or 2-rin Hakuryu crushed stone, and mixtures of these silica sands and Hakuryu crushed stone are more preferable (see Figure 6).

[0085] Regarding the form of powder adhesion to the fiber reinforced sheet 40, it is preferable that the powder is adhered evenly to the surface of the fiber reinforced plastic strands that constitute the fiber reinforced sheet 40. In addition, the amount of powder adhesion (per unit area of ​​the sheet (m 2 per unit), 0.2 to 2 kg / m 2 ) is ensured, the powder may be attached to the entire surface of the fiber-reinforced sheet, or may be attached at regular intervals in the longitudinal direction of the sheet, or may be attached in a patchy pattern. The powder is attached by using an adhesive or binder, or by softening the matrix resin of the fiber-reinforced plastic strands 43 by heating or the like to fuse or weld it.

[0086] <Other Examples of Fiber-Reinforced Sheet 40> An example of the fiber reinforced sheet is not limited to the fiber reinforced sheet 40 shown in FIGS. 5(A) and 5(B).

[0087] The fiber reinforced sheet 40 may be, for example, a fiber reinforced sheet in which a plurality of strip-shaped FRP plates (an example of fiber reinforced plastic wires) containing reinforcing fibers 42 are arranged at equal intervals so as to be parallel to the longitudinal direction and the FRP plates are fixed to each other with a wire fixing material. The width of the strip-shaped FRP plates is preferably 10 to 50 mm, and the plate thickness and spacing between the FRP plates are similar to those of a fiber reinforced sheet using fiber reinforced plastic wires 43.

[0088] The fiber-reinforced sheet 40 is a fiber-reinforced sheet in which a plurality of fiber-reinforced plastic strands 43 containing reinforcing fibers 42 are aligned in the longitudinal direction and fixed to each other with a wire fixing material. The plurality of wires 43 may be bundled into a band shape, arranged with a spacing of 3 to 5 mm between each band, and fixed with the wire fixing material. Note that the band portion where the wires 43 are bundled preferably has a width of approximately 5 to 50 mm, and other shapes and the like are similar to those of the fiber-reinforced plastic strands 43. The structure of the band portion is not particularly limited, and it may be fastened using a wire fixing material, or may be fused using an adhesive.

[0089] <Each step of the reinforcement method> The reinforcing method according to the present embodiment specifically includes a surface preparation step, a primer application step, a mortar application step, and an adhesion step. Each step of the reinforcing method will be described below.

[0090] <Surface preparation process> In the surface preparation step (see FIG. 2), a surface preparation is performed to remove protrusions, attachments, deteriorated layers, etc. from the surface 90A to be reinforced of the structure 90. Removal of the protrusions, attachments, and deteriorated layers can be performed using removal means such as a disk sander, sandblasting, steel shot blasting, or water jet. Note that the surface preparation step is not essential and does not necessarily have to be performed.

[0091] <Primer application process> In the primer application step (see FIG. 3), a water-based epoxy primer 20 is applied to the surface 90A to be reinforced of the structure 90. If a surface preparation step has been performed, the water-based epoxy primer 20 is applied to the surface 90A to be reinforced that has been subjected to the surface preparation.

[0092] By the primer application step, a primer layer 22 made of the water-based epoxy primer 20 is formed on the surface 90A of the structure 90 to be reinforced.

[0093] <Mortar application process> The mortar application step (see FIG. 4) is a step of applying polymer cement mortar 50 to the reinforced surface 90A of the structure 90 to which the water-based epoxy primer 20 has been applied. In the mortar application step, the polymer cement mortar 50 is applied before the water-based epoxy primer 20 hardens.

[0094] In the mortar application step, a binder layer 52 made of polymer cement mortar 50 is formed on the reinforced surface 90A of the structure 90 to which the water-based epoxy primer 20 has been applied (specifically, on the surface of the primer layer 22). The thickness of the binder layer 52 is at least thicker than the fiber-reinforced sheet 40, and is, for example, about 2 mm to 10 mm.

[0095] <Adhesion process> The adhesion step is a step in which, before the applied polymer cement mortar 50 hardens, fiber reinforced sheet 40 is pressed against the applied layer of polymer cement mortar 50 to embed it and adhere it to reinforced surface 90A of structure 90. In this way, fiber reinforced sheet 40 is disposed inside the mortar layer of polymer cement mortar 50.

[0096] The fiber reinforced sheet 40 is pressed with a roller or a rubber spatula, and the air layer at the adhesive interface is expelled from the gaps between the fiber reinforced plastic strands 43, so that the fiber reinforced sheet 40 is embedded in and adhered to the binder layer 52.

[0097] <Effects of this embodiment> The effects of this embodiment will be described.

[0098] In fiber-reinforced sheet 40 of this embodiment, powder is attached to the outer periphery of multiple fiber-reinforced plastic strands 43, and the powder bites into the binder, acting as an anchor, providing an anti-slip effect and enhancing adhesion between fiber-reinforced sheet 40 and polymer cement mortar 50. As a result, fiber-reinforced sheet 40 adheres firmly to polymer cement mortar 50, preventing fiber-reinforced sheet 40 from peeling off from polymer cement mortar 50 before it breaks.

[0099] Here, the amount of powder attached to the outer periphery of the plurality of fiber-reinforced plastic strands 43 is 0.2 kg / m 2 If the powder is less than this, the anti-slip effect of the powder acting as an anchor is small, and the force acting on the attached powder particles is large, resulting in low adhesion between fiber-reinforced sheet 40 and polymer cement mortar 50. As a result, fiber-reinforced sheet 40 may break or peel off from polymer cement mortar 50 before polymer cement mortar 50 experiences cohesive failure.

[0100] In contrast, in the fiber-reinforced sheet 40 of this embodiment, the powder is applied to the periphery of the plurality of fiber-reinforced plastic strands 43 at a density of 0.2 kg / m 2Since the powder adheres to the surface, the anti-slip effect of the powder maintains high adhesion between the fiber reinforced sheet 40 and the polymer cement mortar 50 .

[0101] Here, the fiber-reinforced sheet 40 is a sheet in which multiple fiber-reinforced plastic strands 43 are aligned in a curtain-like shape in the longitudinal direction, so when powder is attached to the outer periphery of the multiple fiber-reinforced plastic strands 43, the spaces between the multiple fiber-reinforced plastic strands 43 become narrower.

[0102] In contrast, in the fiber-reinforced sheet 40 of the present embodiment, the powder is applied to the periphery of the plurality of fiber-reinforced plastic strands 43 at a density of 2.0 kg / m 2 The fibers are adhered at intervals of 0.5 mm or less, with a minimum gap of 0.5 mm or more, and the average particle size of the powder is 0.900 mm or less. Therefore, when the fiber-reinforced sheet 40 is embedded and bonded to the polymer cement mortar 50 applied to the reinforced surface 90A of the structure 90, the polymer cement mortar 50 can easily pass through the gaps between the fiber-reinforced plastic wires 43 even if the gaps between the fiber-reinforced plastic wires 43 are narrow. As a result, poor application (poor adhesion between the fiber-reinforced sheet 40 and the polymer cement mortar 50) is suppressed, and the fiber-reinforced sheet 40 can be prevented from peeling off from the polymer cement mortar 50 before it breaks.

[0103] In addition, in the fiber reinforced sheet 40 of this embodiment, the gap distance between the fiber reinforced plastic strands 43 without taking powder into consideration is more than 3 mm and 15 mm or less.

[0104] Here, if the gap spacing between the fiber-reinforced plastic strands 43 is 3 mm or less, the spacing between the fiber-reinforced plastic strands 43 is narrow, and it is difficult to adjust the minimum gap spacing to 0.5 mm or more for multiple fiber-reinforced plastic strands 43 with powder attached to the outer periphery.

[0105] On the other hand, if the gap distance between the fiber reinforced plastic strands 43 exceeds 15 mm, the number of fiber reinforced plastic strands 43 per unit area of ​​the fiber reinforced sheet 40 decreases, and the reinforcing effect decreases.

[0106] In contrast, in this embodiment, as described above, the gap spacing between the fiber-reinforced plastic strands 43 in the fiber-reinforced sheet 40 is greater than 3 mm and not greater than 15 mm, so it is easy to adjust the minimum gap spacing to 0.5 mm or more while suppressing a decrease in the reinforcing effect.

[0107] Furthermore, in the fiber-reinforced sheet 40 of this embodiment, the gap spacing between the fiber-reinforced plastic strands 43, ignoring the powder, is larger than the diameter of the powder, and the ratio of the diameter of the fiber-reinforced plastic strands 43, the gap spacing ignoring the powder, and the diameter of the powder is 1:0.5~5:0.03~1.

[0108] Here, if the ratio of the gap spacing between the fiber reinforced plastic strands 43 to the diameter of the fiber reinforced plastic strands 43 is less than 0.5, the space between the fiber reinforced plastic strands 43 will be relatively narrow, making it difficult for the binder to pass between the fiber reinforced plastic strands 43.

[0109] On the other hand, if the ratio of the gap spacing between the fiber-reinforced plastic wires 43 to the diameter of the fiber-reinforced plastic wires 43 exceeds 5, the area of ​​the fiber-reinforced plastic wires 43 per unit area of ​​the fiber-reinforced sheet 40 decreases, and the reinforcing effect decreases.

[0110] Furthermore, if the ratio of the diameter of the powder to the diameter of fiber-reinforced plastic strands 43 is less than 0.03, the anti-slip effect of the powder is small, and the adhesion between fiber-reinforced sheet 40 and polymer cement mortar 50 is low. As a result, fiber-reinforced sheet 40 may peel off from polymer cement mortar 50 before reaching its breaking strength.

[0111] On the other hand, if the ratio of the diameter of the powder to the diameter of fiber-reinforced plastic strands 43 exceeds 1, the spaces between fiber-reinforced plastic strands 43 become narrower. As a result, polymer cement mortar 50 has difficulty passing through the spaces between fiber-reinforced plastic strands 43, which may result in poor construction.

[0112] In contrast, in the present embodiment, as described above, the ratio of the diameter of fiber-reinforced plastic wires 43, the gap between fiber-reinforced plastic wires 43, and the diameter of the powder is 1:0.5-5:0.03-1, so that the anti-slip effect of the powder maintains high adhesion between fiber-reinforced sheet 40 and polymer cement mortar 50, making it easy for polymer cement mortar 50 to pass between fiber-reinforced plastic wires 43.

[0113] As a result, poor application (poor adhesion between fiber reinforced sheet 40 and polymer cement mortar 50) is suppressed, and fiber reinforced sheet 40 is prevented from peeling off from polymer cement mortar 50 before it reaches its breaking strength.

[0114] <Evaluation test> In this test, the reinforcing effect of the fiber-reinforced sheet 40 according to this embodiment was evaluated. Specifically, in this test, Examples 1 to 7 and Comparative Examples 1 to 7 were evaluated as follows.

[0115] [One-sided shear test] In this test, a single-sided shear test was conducted using a JIS concrete slab (equivalent to structure 90), fiber-reinforced sheet 40, water-based epoxy primer 20, and polymer cement mortar 50.

[0116] The reinforcing effect of the fiber-reinforced sheet 40 on a concrete body (corresponding to structure 90) has been confirmed when the fiber-reinforced sheet 40 itself is used for reinforcement using conventional epoxy resin. Here, the reinforcing effect was confirmed by evaluating the adhesion performance between the concrete body and the fiber-reinforced sheet when a non-hazardous material, which differs from conventional construction methods, was used using a one-sided tensile shear test.

[0117] Test specimen 100 for the single-sided shear test was prepared by scraping a 30 cm square JIS concrete slab 90, applying water-based epoxy primer 20, applying polymer cement mortar 50 in three rows, each 4 cm wide and 5 mm thick, and then embedding three rows of fiber-reinforced sheet 40, also cut to a 4 cm wide and 60 cm long piece, so that one side protruded. After curing for two weeks at 20°C, tab 99 made of epoxy resin and aramid fiber sheet was attached to one end of fiber-reinforced sheet 40 (see FIG. 7 ). As shown in FIG. 8 , the single-sided shear test was performed on test specimen 100 using a universal testing machine and test specimen fixing jig 102 to evaluate the failure load and failure mode. Evaluation of the integrity of the reinforcing fiber sheet and the concrete member was performed with n=3.

[0118] The criteria for determining pass / fail were the measured interfacial peel fracture energy Gf and the observation of the fracture mode, with the former being 0.5 N / mm and the latter being that no "bond break between the fiber-reinforced sheet (CFSS) and the bonding material (PCM)" was observed in any of the test pieces.

[0119] [Workability test of polymer cement mortar 50] The workability of Polymer Cement Mortar 50 was evaluated for its passability and trowel slipperiness using the following method. A 5mm thick coat of mortar was applied to a formwork measuring 40mm long x 250mm long x 5mm thick, and a metal trowel was then slid over the sand-covered CFSS. The passability of the mortar and the trowel slipperiness were evaluated using the following criteria:

[0120] ·Transparency 〇: Buried in 0 to 15 seconds △: Buried in 15 to 30 seconds ×: 30 seconds or more

[0121] Trowel slippage Good: Good sliding and no sand falling off △: High resistance, sand does not fall ×: High resistance, sand falls

[0122] [Polymer cement mortar 50] Polymer cement mortar 50 was used, which was prepared based on Refremorset D manufactured by Sumitomo Osaka Cement Co., Ltd. This polymer cement mortar 50 was mixed with 1.1 wt% high-strength polyethylene reinforcing fiber with a length of 9 mm and an aspect ratio of 750, and the mortar had a maximum fine aggregate diameter of 0.45 mm, an FM value of 1.02, and a W / P ratio of 22.0 wt%.

[0123] [Water-based Epoxy Primer 20] FP Primer FP-EE from Nippon Steel Chemical & Material Co., Ltd. was used as the water-based epoxy primer 20. This primer is a two-component primer consisting of a base agent and a curing agent.

[0124] [Fiber reinforced sheet 40] The fiber-reinforced sheet 40 was produced using a strand sheet as follows. <Production of raw material (strand sheet before sand adhesion)> The reinforcing fibers were PAN-based carbon fiber strands with an average diameter of 6 μm and a number of strands of 12,000. The matrix resin described below was impregnated into the uncured resin-impregnated reinforcing fiber bundle after resin impregnation. Six strands were twisted at 18 turns / m to form a single strand, which was then cured to produce a fiber-reinforced plastic wire in the fiber-reinforced sheet. The resin impregnation amount of the fiber-reinforced plastic wire was 40 wt %, and the diameter after curing was 2.2 mm. Next, multiple fiber-reinforced plastic strands were aligned in one direction to achieve the desired fiber content and arranged in a blind shape, and then the multiple fiber-reinforced plastic strands arranged in the blind shape were fixed by weaving nylon thread as a wire fixing material at regular intervals in the direction perpendicular to the longitudinal direction of the strands to be processed into a sheet, thereby creating a raw roll of blind-shaped fiber-reinforced sheet 1. The raw roll of fiber-reinforced sheet produced in this manner had a width (W) of 500 mm and a length (L) of 100 m. Corresponding to each example and comparative example, the gap between the fiber-reinforced plastic strands was adjusted within the range of 3.0 to 16.8 mm.

[0125] <Matrix resin> As the matrix resin, the following room temperature curing epoxy resin was used. Epoxy resin YD-128 100phr ED-503 67phr Hardener: Dicyandiamide 12 phr Accelerator DCMU 2phr

[0126] <Powder adhesion> The powder was attached to the fiber-reinforced sheet raw material by applying an epoxy resin adhesive with a roller, and then applying the powder at a rate of 0.1 to 2.4 kg / m according to each example and comparative example. 2 The adhesive was spread on both sides of the raw sheet using a screen so that the amount of adhesive adhered would be in the range of 1.0 to 1.5 mm, and then the adhesive was cured.

[0127] <Method for measuring gaps in sand-covered CFSS> The gap spacing of the sand-attached CFSS is the gap spacing between the fiber-reinforced plastic strands 43 in a powder-attached state. The gap spacing of the sand-attached CFSS was measured using a calibrated vernier caliper at 10 locations per 100 m of powder-attached fiber-reinforced sheet. Note that when the gaps between the fiber-reinforced plastic strands 43 are connected by powder, the minimum spacing is set to 0 mm, and the maximum spacing was measured at locations other than those mentioned above.

[0128] [Example 1] In Example 1, the diameter of the fiber reinforced plastic strand 43 is 2.2 mm, and the fiber weight is 450 g / m 2 The raw material (strand sheet before sand adhesion) was used, with the gap between the wires (gap not considering powder) being approximately 5.4 mm. For this roll, 1 m of silica sand No. 8 (average particle size 0.073 mm) is added. 2 The sand-attached CFSS was attached with epoxy resin adhesive at a rate of 1.0 kg per square meter. The maximum gap between the sand-attached CFSS was 5.10 mm and the minimum gap was 4.40 mm. In the construction test, both passability and trowel sliding were good. In the one-way shear test, the average breaking load was 23.5kN, the interface peel fracture energy Gf was 1.49N / mm, and the fracture mode was cohesive failure of the newly cast mortar.

[0129] [Example 2] In Example 2, the diameter of the fiber reinforced plastic strand 43 is 2.2 mm, and the fiber basis weight is 450 g / m 2 The raw material (strand sheet before sand adhesion) was used, with the gap between the wires (gap not considering powder) being approximately 5.4 mm. For this base cloth, 1 m of silica sand No. 6 (average particle size 0.294 mm) was added. 2 The sand-attached CFSS was attached with epoxy resin adhesive at a rate of 0.4 kg per square meter. The maximum gap between the sand-attached CFSS was 4.81 mm, and the minimum gap was 3.90 mm. In the construction test, both passability and trowel sliding were good. In the one-way shear test, the average breaking load was 19.9 kN, the interface peel fracture energy Gf was 1.08 N / mm, and the fracture mode was cohesive failure of the newly placed mortar.

[0130] [Example 3] In Example 3, the diameter of the fiber reinforced plastic strand 43 is 2.2 mm, and the fiber basis weight is 450 g / m 2 The raw material (strand sheet before sand adhesion) was used, with the gap between the wires (gap not considering powder) being approximately 5.4 mm. For this base cloth, 1 m of silica sand No. 6 (average particle size 0.294 mm) was added. 2 The sand-attached CFSS was attached with epoxy resin adhesive at a rate of 0.9 kg per square meter. The maximum gap between the sand-attached CFSS was 4.40 mm and the minimum gap was 3.90 mm. In the construction test, both passability and trowel sliding were good. In the one-way shear test, the average breaking load was 20.0 kN, the interface peel fracture energy Gf was 1.08 N / mm, and the fracture mode was cohesive failure of the newly cast mortar.

[0131] [Example 4] In Example 4, the diameter of the fiber reinforced plastic strand 43 is 2.2 mm, and the fiber basis weight is 450 g / m 2 The raw material (strand sheet before sand adhesion) was used, with the gap between the wires (gap not considering powder) being approximately 5.4 mm. For this roll, 1 m of silica sand No. 4 (average particle size 0.887 mm) is added. 2 The sand-attached CFSS was attached with an epoxy resin adhesive at a rate of 1.6 kg per square meter. The maximum gap between the sand-attached CFSS was 3.00 mm and the minimum gap was 2.20 mm. In the construction test, the passability was good and the trowel sliding was rated as fair. In the one-way shear test, the average breaking load was 26.1 kN, the interface peel fracture energy Gf was 1.90 N / mm, and the fracture mode was cohesive failure of the newly cast mortar.

[0132] [Example 5] In Example 5, the diameter of the fiber reinforced plastic strand 43 is 2.2 mm, and the fiber basis weight is 300 g / m 2 The raw material (strand sheet before sand adhesion) was used, with the gap between the wires (gap not considering powder) being approximately 10.0 mm. For this base cloth, 1 m of silica sand No. 6 (average particle size 0.294 mm) was added. 2 The sand-attached CFSS was attached with epoxy resin adhesive at a rate of 0.9 kg per square meter. The maximum gap between the sand-attached CFSS was 8.71 mm, and the minimum gap was 7.70 mm. In the construction test, both passability and trowel sliding were good. In the one-way shear test, the average breaking load was 20.3 kN, the interface peel fracture energy Gf was 1.13 N / mm, and the fracture mode was cohesive failure of the newly cast mortar.

[0133] [Example 6] In Example 6, the diameter of the fiber reinforced plastic strand 43 is 2.2 mm, and the fiber basis weight is 700 g / m 2 The raw material (strand sheet before sand adhesion) was used, in which the gap between the wires (gap not considering powder) was approximately 3.0 mm. For this base cloth, 1 m of silica sand No. 6 (average particle size 0.294 mm) was added. 2 The sand-attached CFSS was attached with an epoxy resin adhesive at a rate of 0.8 kg per square meter. The maximum gap between the sand-attached CFSS was 2.14 mm, and the minimum gap was 0.65 mm. In the construction test, passability was rated as fair, and trowel sliding was good. In the one-way shear test, the average breaking load was 19.4 kN, the interface peel fracture energy Gf was 1.02 N / mm, and the fracture mode was cohesive failure of the newly cast mortar.

[0134] [Example 7] In Example 7, the diameter of the fiber reinforced plastic strand 43 is 2.2 mm, and the fiber basis weight is 450 g / m 2 The raw material (strand sheet before sand adhesion) was used, with the gap between the wires (gap not considering powder) being approximately 5.4 mm. For this roll, 1 rin of crushed stone (average particle size 0.4 mm) is added to 1 m 2 The sand-attached CFSS was attached with an epoxy resin adhesive at a rate of 1.0 kg per square meter. The maximum gap between the sand-attached CFSS was 4.80 mm, and the minimum gap was 3.55 mm. In the construction test, both passability and trowel sliding were good. In the one-way shear test, the average breaking load was 19.8kN, the interface peel fracture energy Gf was 1.06N / mm, and the fracture mode was cohesive failure of the newly cast mortar.

[0135] [Comparative Example 1] In Comparative Example 1, the diameter of the fiber reinforced plastic strand 43 is 2.2 mm, and the fiber basis weight is 450 g / m 2 The raw material (strand sheet before sand adhesion) was used, with the gap between the wires (gap not considering powder) being approximately 5.4 mm. For this base cloth, 1 m of silica sand No. 6 (average particle size 0.294 mm) was added. 2 The sand-attached CFSS was attached with epoxy resin adhesive at a rate of 0.1 kg per square meter. The maximum gap between the sand-attached CFSS was 4.90 mm, and the minimum gap was 3.90 mm. In the construction test, both passability and trowel sliding were good. In the one-way shear test, the average breaking load was 22.6 kN and the interface peel fracture energy Gf was 1.40 N / mm, but the fracture mode was NG mode in some test pieces, where the wire rod was pulled out of the mortar, resulting in interface fracture ("CFSS / PCM bond failure").

[0136] Comparative Example 2 In Comparative Example 2, the diameter of the fiber reinforced plastic strand 43 is 2.2 mm, and the fiber basis weight is 450 g / m 2 The raw material (strand sheet before sand adhesion) was used, with the gap between the wires (gap not considering powder) being approximately 1.3 mm. For this base cloth, 1 m of silica sand No. 6 (average particle size 0.294 mm) was added. 2 The sand-attached CFSS was attached with an epoxy resin adhesive at a rate of 1.0 kg per square meter. The maximum gap between the sand-attached CFSS was 0.70 mm and the minimum gap was 0.10 mm. In the construction test, the passability was poor, but the trowel sliding was good. In the one-way shear test, the mortar itself did not pass through the fiber-reinforced sheet, and when the mortar hardened, it separated at the fiber-reinforced sheet, making it unsuitable for the test.

[0137] Comparative Example 3 In Comparative Example 3, the diameter of the fiber reinforced plastic strand 43 is 2.2 mm, and the fiber basis weight is 450 g / m 2 The raw material (strand sheet before sand adhesion) was used, with the gap between the wires (gap not considering powder) being approximately 1.3 mm. For this base cloth, 1 m of silica sand No. 3 (average particle size 1.344 mm) was added. 2 The sand was attached using epoxy resin adhesive at a rate of 1.0 kg per CFSS. The maximum gap between the sand-attached CFSS was 0.10 mm and the minimum gap was 0.00 mm. In the construction test, both passability and trowel sliding were poor. In the one-way shear test, the mortar itself did not pass through the fiber-reinforced sheet, and when the mortar hardened, it separated at the fiber-reinforced sheet, making it unsuitable for the test.

[0138] Comparative Example 4 In Comparative Example 4, the diameter of the fiber reinforced plastic strand 43 is 2.2 mm, and the fiber basis weight is 450 g / m 2 The raw material (strand sheet before sand adhesion) was used, with the gap between the wires (gap not considering powder) being approximately 5.4 mm. For this roll, 1 m of silica sand No. 2 (average particle size 1.59 mm) is added. 2 The sand-attached CFSS was attached with an epoxy resin adhesive at a rate of 2.4 kg per square meter. The maximum gap between the sand-attached CFSS was 2.60 mm and the minimum gap was 0.00 mm. In the construction test, both passability and trowel sliding were poor. In the one-way shear test, the mortar itself did not pass through the fiber-reinforced sheet, and when the mortar hardened, it separated at the fiber-reinforced sheet, making it unsuitable for the test.

[0139] Comparative Example 5 In Comparative Example 5, the diameter of the fiber reinforced plastic strand 43 is 2.2 mm, and the fiber basis weight is 450 g / m 2 The raw material (strand sheet before sand adhesion) was used, with the gap between the wires (gap not considering powder) being approximately 5.4 mm. For this base cloth, 1 m of silica sand No. 3 (average particle size 1.344 mm) was added. 2 The sand was attached using epoxy resin adhesive at a rate of 2.3 kg per square meter. The maximum gap between the sand-attached CFSS was 3.00 mm and the minimum gap was 0.00 mm. In the construction test, both passability and trowel sliding were poor. In the one-way shear test, the mortar itself did not pass through the fiber-reinforced sheet, and when the mortar hardened, it separated at the fiber-reinforced sheet, making it unsuitable for the test.

[0140] Comparative Example 6 In Comparative Example 6, the diameter of the fiber reinforced plastic strand 43 is 2.2 mm, and the fiber basis weight is 180 g / m 2 The raw material (strand sheet before sand adhesion) was used, with the gap between the wires (gap not considering powder) being approximately 16.8 mm. For this base cloth, 1 m of silica sand No. 6 (average particle size 0.294 mm) was added. 2 The sand-attached CFSS was attached using epoxy resin adhesive at a rate of 1.0 kg per square meter. The maximum gap between the sand-attached CFSS was 16.46 mm, and the minimum gap was 15.10 mm. In the application test, both passability and trowel sliding were good. In the one-way shear test, the failure mode was breakage of the carbon fiber.

[0141] Comparative Example 7 In Comparative Example 7, the diameter of the fiber reinforced plastic strand 43 is 2.2 mm, and the fiber basis weight is 450 g / m 2 The raw material (strand sheet before sand adhesion) was used, with the gap between the wires (gap not considering powder) being approximately 5.4 mm. In Comparative Example 7, instead of applying the powder, a water-based epoxy primer was applied directly to the fiber-reinforced sheet. 2 After drying for 30 minutes in a 20°C environment, a trial test and a one-way shear test were conducted. In the construction test, both passability and trowel sliding were good. In the one-way shear test, the average breaking load was 25.1 kN and the interface peel fracture energy Gf was 1.71 N / mm, but the fracture mode was NG mode in all test pieces, where the wire rod was pulled out of the mortar, resulting in interface fracture ("CFSS / PCM bond failure").

[0142] [Test Results of Examples 1 to 7 and Comparative Examples 1 to 7] The test results for Examples 1 to 7 and Comparative Examples 1 to 7 are shown in Table 1 in Figure 9. As shown in Table 1, in Examples 1 to 7, the interfacial peel fracture energy calculated from the results of the single-sided shear test was 0.5 N / mm or more, which is better than that of Comparative Examples 1 to 7, and none of the test specimens showed interfacial fracture ("CFSS / PCM bond failure") in which the wires of the strand sheet were pulled out of the mortar, confirming that there was a sufficient reinforcing effect. Although the fracture mode in Comparative Examples 1 and 7 was NG mode, the interfacial peel fracture energy exceeded 0.5 N / mm. This is due to the frictional force between the fiber-reinforced sheet 40 and the peeled powder and binder. Therefore, in cases where a dynamic load is applied, such as in a wheel load running test described below, the fiber-reinforced sheet 40 easily peels off from the binder before breaking, resulting in NG.

[0143] <Deck wheel load running test> In order to finally confirm the reinforcing effect of the fiber-reinforced sheet according to this embodiment, a wheel load running test was conducted using a full-scale concrete deck specimen (see Figures 12 and 13) with reference to the following previous literature.

[0144] Previous literature: Okada et al., "Effect of deck reinforcement using lattice-arranged carbon fiber sheets," Proceedings of the 3rd Road Bridge Deck Symposium, pp. 175-180

[0145] This test is a test method for evaluating the fatigue durability of a deck by applying a load as shown in Figure 11 and moving a full-scale deck specimen back and forth.This is an evaluation method that has also been used in previous studies to evaluate the fatigue durability of decks reinforced with carbon fiber sheets using epoxy resin adhesive.

[0146] In this test, in order to confirm the reinforcing effect of the fiber-reinforced sheet according to this embodiment, a wheel load running test was conducted on an ordinary RC deck reinforced using this reinforcement method, with the same specimen dimensions and test conditions as in previous literature 1.

[0147] The dimensions of the specimen used in this test and the arrangement of the rebars are as shown in Figure 13. The concrete mix is ​​as shown in the table in Figure 14.

[0148] The test specimen was 2000 mm (length perpendicular to the bridge axis) × 3000 mm (length in the bridge axis direction) × 180 mm (thickness), and had a deck slab with haunches (50 mm) at the ends. Fiber-reinforced sheets 40 of Example 1 were attached to the deck slab using polymer cement mortar 50, with 250 mm wide pieces spaced 150 mm apart, one layer vertically and one layer horizontally (see Figure 12). After curing was complete, a wheel load running test was conducted.

[0149] The loading conditions in this test were the same as in previous studies, with the staircase loading shown in Figure 15. The horizontal axis represents the number of runs, and the vertical axis represents the wheel load, with a load of 150kN applied for the initial 100,000 runs, 180kN thereafter for 800,000 runs, 210kN for the next 1,000,000 runs, and then 210kN for the next 1,050,000, 1,150,000, and 1,200,000 runs, with the load then increasing by 30kN each time, and the fatigue durability was evaluated based on the increase in deflection in the center of the deck.

[0150] The test results, as shown in Figure 16, confirmed a reinforcing effect that compares favorably with previous research. It was estimated that the concrete floor slab (fireproof floor slab reinforcement) using the fiber-reinforced sheet according to this embodiment has a lifespan that is 30 times longer than that of floor slab reinforcement using conventional methods, demonstrating a sufficient reinforcing effect.

[0151] The fiber-reinforced sheet 40 of the present invention is not limited to application to the reinforcement method according to the above embodiment, but can also exert a similarly favorable reinforcing effect when applied to a fiber-reinforced sheet adhesive construction method that uses primers, unevenness correction materials, or epoxy resin-based binders, which are considered to be hazardous materials.

[0152] The present invention is not limited to the above-described embodiment, and various modifications, changes, and improvements are possible within the scope of the gist of the present invention. As an example, to prevent defects in the binder-coated surface, such as the amine blushing phenomenon that may occur when an epoxy resin-based resin binder is used, a release sheet that can be impregnated with the binder but can be peeled off together with the surface layer of the coated surface after curing may be removably fixed to one side of the fiber-reinforced sheet 40. [Explanation of symbols]

[0153] 20 Water-based epoxy primer 22 Primer layer 40 Fiber-reinforced sheet 42 Reinforced Fiber 43 Fiber-reinforced plastic wire 45 Wire fixing material 47 Matrix Resin 50 Polymer cement mortar 52 Binder layer 90 Structures 90A Reinforced surface

Claims

1. A fiber-reinforced sheet that is adhered to a surface of a structure by being embedded in a bonding material applied to the surface of the structure, A plurality of fiber-reinforced plastic strands containing reinforcing fibers are aligned in a longitudinal direction in a curtain-like shape, and the fiber-reinforced plastic strands are fixed to each other with a strand fixing material, A powder having an average particle size of 0.900 mm or less is applied to the outer periphery of the plurality of fiber-reinforced plastic strands at a pressure of 0.2 to 2.0 kg / m 2 Attached at The minimum gap between adjacent fiber-reinforced plastic strands in the powder-adhered state is 0.5 mm or more. Fiber reinforced sheet.

2. The gap between the fiber-reinforced plastic strands, excluding the powder, is greater than 3 mm and less than 15 mm. The fiber-reinforced sheet according to claim 1 .

3. A gap between the fiber-reinforced plastic strands, excluding the powder, is larger than a diameter of the powder, The ratio of the diameter of the fiber-reinforced plastic strand, the gap interval not taking into account the powder, and the diameter of the powder is 1:0.5-5:0.03-1. The fiber-reinforced sheet according to claim 1 .

4. The powder is No. 4 to No. 8 silica sand and mixtures thereof, 1-2 rin limestone powder and its mixture Either The fiber-reinforced sheet according to claim 1 .

5. The fiber reinforced plastic strand is The reinforcing fibers are yarns made by twisting together a plurality of fiber bundles aligned in one direction. The fiber-reinforced sheet according to claim 1 .

6. The wire fixing material is A plurality of weft threads are used to weave the plurality of fiber-reinforced plastic strands in a direction perpendicular to the longitudinal direction of the fiber-reinforced plastic strands. The fiber-reinforced sheet according to claim 1 .

7. The weft yarn is The yarn is made of glass fiber or organic fiber. The fiber-reinforced sheet of claim 6.

8. The reinforcing fibers of the fiber-reinforced plastic strand include inorganic fibers selected from carbon fibers, glass fibers, basalt fibers, and fly ash fibers; metal fibers selected from boron fibers, titanium fibers, and steel fibers; and an organic fiber selected from aramid, polyparaphenylene benzbisoxazole, polyamide, polyarylate, and polyester, Used alone or in combination The fiber-reinforced sheet according to claim 1 .

9. The fiber-reinforced plastic strand is formed by hardening a matrix resin impregnated in the reinforcing fibers, The matrix resin includes a thermosetting resin selected from room temperature curing or thermosetting epoxy resins, vinyl ester resins, acrylic resins, unsaturated polyester resins, and phenolic resins; Alternatively, a thermoplastic resin selected from nylon, vinylon, and phenoxy resin is used. The fiber-reinforced sheet according to claim 1 .

Citation Information

Patent Citations

  • Reinforcement of structure

    JP1991224901A

  • Structure reinforcing method

    JP2008063758A

  • Method for reinforcing structure

    JP2011208352A